2009
DOI: 10.1007/s10833-009-9106-1
|View full text |Cite
|
Sign up to set email alerts
|

Youth engagement in high schools: Developing a multidimensional, critical approach to improving engagement for all students

Abstract: What keeps students interested and engaged in school? Unfortunately, in today's climate of increased rigor in classrooms, we are simultaneously losing sight of the need to provide students with an education that is both challenging and stimulating. In this paper, we discuss youth disengagement and offer suggestions to improve our overall knowledge of academic engagement issues. We discuss the historical concept of engagement, more specifically, its shift from a uni-dimensional to multidimensional concept, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 67 publications
3
63
0
4
Order By: Relevance
“…Recent research in two neighbouring countries, Malawi (Kamwendo 2010) and Uganda (Jones 2011) shows that insights gained from ethnographic studies on female students can unfold the construction of gender and gendered experiences in education and thereby contribute to achievement of equity targets. Previous research further suggests that student voice is essential for the assessment of educational opportunities and critical aspects when aiming for meaningful educational change (Yonezawa, Jones and Joselowsky, 2009;Mitra and Gross, 2009;Warrington and Kiragu, 2012). Inspired by the evident potential of student voice work (McLeod, 2011), and student engagement for prevention of dropout (Yonezawa, 2009), this paper focuses on the female students' views on secondary education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research in two neighbouring countries, Malawi (Kamwendo 2010) and Uganda (Jones 2011) shows that insights gained from ethnographic studies on female students can unfold the construction of gender and gendered experiences in education and thereby contribute to achievement of equity targets. Previous research further suggests that student voice is essential for the assessment of educational opportunities and critical aspects when aiming for meaningful educational change (Yonezawa, Jones and Joselowsky, 2009;Mitra and Gross, 2009;Warrington and Kiragu, 2012). Inspired by the evident potential of student voice work (McLeod, 2011), and student engagement for prevention of dropout (Yonezawa, 2009), this paper focuses on the female students' views on secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research further suggests that student voice is essential for the assessment of educational opportunities and critical aspects when aiming for meaningful educational change (Yonezawa, Jones and Joselowsky, 2009;Mitra and Gross, 2009;Warrington and Kiragu, 2012). Inspired by the evident potential of student voice work (McLeod, 2011), and student engagement for prevention of dropout (Yonezawa, 2009), this paper focuses on the female students' views on secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…Both intrinsic (i.e., learning for enjoyment) and extrinsic (i.e., learning as a means to an end) forms of motivation decrease across the high school transition (Otis, Grouzet, & Pelletier, 2005) and are lower than motivation levels of elementary school and college students (Martin, 2009). Adolescents' decreased investment in school is concerning given their newfound freedom; students who are not academically motivated may not pay attention, complete their work, or even attend school (Yonezawa, Jones, & Joselowsky, 2009). It is vital, then, to investigate the nature of high school students' motivation, the contextual forces that may predict it, and the school outcomes that may flow from it.…”
mentioning
confidence: 99%
“…Originally, the engagement of students was viewed simply as a static concept, made up of three separate and disparate components, which is characterized by a linear relationship between the curriculum and developing engagement in the learning process (Yonezawa, Jones, & Joselowsky, 2009). In earlier research, engagement has been identified by behavioral dimension, through the behavior of students that could be easily noticed while they neglected the dimensions dependent on the context (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive dimension of student engagement was explored especially in the field of psychology, where it has been closely identified with motivational processes and the development of metacognitive strategies. Emotional engagement, which was also explored as a separate dimension, related to the emotional reactions of students in the process of teaching and learning, such as interest, boredom, happiness, sadness and anxiety (Yonezawa, Jones, & Joselowsky, 2009). Today the authors represent a multidimensional approach in their research studies, using two or three dimensions as indicators of student engagement (Appleton, et.…”
Section: Introductionmentioning
confidence: 99%